Elastocaloric can cooler: an exemplary technology transfer to use case application - Ehl, L.; Scherer, N.; Zimmermann, D.; Trofimenko, I.; Molitor, P.; Kirsch, S.-M.; Louia, F.; Motzki, P. (Frontiers in Materials, 2025)
The elastocaloric effect offers a promising alternative to conventional compressor-based heating and cooling systems. This technology leverages solid-state phase transformations with high energy densities, eliminating the need for environmentally harmful refrigerants. As a result, elastocaloric systems can be developed for both heating and cooling applications that are sustainable, highly efficient, and scalable. In this study, the first elastocaloric “mini-fridge” operating under tensile load is developed, using air as heat transfer medium. This system is based on the world’s first continuously operating air-to-air elastocaloric machine demonstrator. The primary focus of this study is to investigate the transition from a generic technology demonstrator to an application-oriented system. A simulation tool enables investigation and optimization of various machine parameters such as material dimensions, load profiles, and latent heats for the intended application. The application targeted in this study is a “mini-fridge” designed to cool a standard 0.25 L beverage can. Shape memory alloy wire bundles are subjected to loading and unloading cycles by a patented energy converter. To effectively harness the latent heat released during phase transformation, the air must be optimally directed over the wire bundles. The cooling process is achieved by continuously circulating air around the bundles, progressively cooling a volume. The simulation tool is employed to determine the optimal geometric and process parameters for this system. The study aims to develop the first continuously operating elastocaloric “mini-fridge” with an internal cooling volume. To validate the entire setup, the inner chamber is equipped with temperature sensors to monitor the cooling performance. These sensors are strategically placed along the axis of rotation to measure the temperature as air enters and exits the chamber. The initial measurements achieved a temperature difference of approximately 3.5 K within the cooling chamber versus a simulated value 8.7 K, which did not include all possible losses present in the system. The simulation suggests a system COP at steady state of 5.8, which must be experimentally verified in future work.